Strength Lies in Diversity: How Community Diversity Limits Salmonella Abundance in the Chicken Intestine - Pedroso, Adriana A.; Lee, Margie D.; Maurer, John J. (Frontiers in Microbiology, 2021)
The transfer of the intestinal microbiota from adult to juvenile animals reduces Salmonella prevalence and abundance. The mechanism behind this exclusion is unknown however certain member species may exclude or promote pathogen colonization; and Salmonella abundance in chickens correlates with intestinal community composition. In this study, newly hatched chicks were colonized with Salmonella Typhimurium, and 16S rDNA libraries were generated from the cecal bacterial community at 21, 28, 35, and 42 days of age. Salmonella was quantified by real-time PCR. Operational taxonomic units (OTUs) were assigned, and taxonomic assignments were made using the Ribosomal Database Project. Bacterial diversity was inversely proportional to the Salmonella abundance in the chicken cecum (p < 0.01). In addition, cecal communities with no detectable Salmonella (exclusive community) displayed an increase in the abundance of OTUs related to specific clostridial families (Ruminococcaceae, Eubacteriaceae, and Oscillospiraceae), genera (Faecalibacterium and Turicibacter) and member species (Ethanolidenens harbineses, Oscilibacter ruminanticum, and Faecalibacterium prausnitzii). For cecal communities with high Salmonella abundance (permissive community), there was a positive correlation with the presence of unclassified Lachnospiraceae, clostridial genera Blautia and clostridial species Roseburia hominis, Eubacterium biforme, and Robinsoniella peoriensis. Our findings strongly support the link between the intestinal bacterial species diversity and the presence of specific member species with Salmonella abundance in the chicken ceca. Exclusive bacterial species could prove effective as direct-fed microbials for reducing Salmonella in poultry while permissive species could be used to predict which birds will be super-shedders.